THE EVOLVING ROLE OF DIGITAL TECHNOLOGIES IN THE TEACHER'S WORK (Web of Teachers: Inderscience Research, 2024)
This article examines the multifaceted role of digital technologies in the work of a teacher, the ways in which digital technologies influence the work of teachers.